A systematic scoping review of study methodology for randomized controlled trials investigating probiotics in athletic and physically active populations - Alex E. Mohr; David B. Pyne; Geovana Silva Fogaça Leite; Deborah Akins; Jamie Pugh (Elsevier, 2024)
Background: The purported ergogenic and health effects of probiotics have been a topic of great intrigue among researchers, practitioners, and the lay public alike. There has also been an increased research focus within the realm of sports science and exercise medicine on the athletic gut microbiota. However, compared to other ergogenic aids and dietary supplements, probiotics present unique study challenges. The objectives of this systematic scoping review were to identify and characterize study methodologies of randomized controlled trials investigating supplementation with probiotics in athletes and physically active individuals. Methods: Four databases (MEDLINE, CINAHL, Cochrane CENTRAL, and Cochrane Database of Systematic Reviews) were searched for randomized controlled studies involving healthy athletes or physically active individuals. An intervention with probiotics and inclusion of a control and/or placebo group were essential. Only peer-reviewed articles in English were considered, and there were no date restrictions. Results were extracted and presented in tabular form to detail study protocols, characteristics, and outcomes. Bias in randomized controlled trials was determined with the RoB 2.0 tool. Results: A total of 45 studies were included in the review, with 35 using a parallel group design and 10 using a cross-over design. Approximately half the studies used a single probiotic and the other half a multi-strain preparation. The probiotic dose ranged from 2 × 108 to 1 × 1011 colony forming units daily, and the length of intervention was between 7 and 150 days. Fewer than half the studies directly assessed gastrointestinal symptoms, gut permeability, or the gut microbiota. The sex ratio of participants was heavily weighted toward males, and only 3 studies exclusively investigated females. Low-level adverse events were reported in only 2 studies, although the methodology of reporting varied widely. The risk of bias was generally low, although details on randomization were lacking in some studies. Conclusion: There is a substantial body of research on the effects of probiotic supplementation in healthy athletes and physically active individuals. Considerable heterogeneity in probiotic selection and dosage as well as outcome measures has made clinical and mechanistic interpretation challenging for both health care practitioners and researchers. Attention to issues of randomization of participants, treatments and interventions, selection of outcomes, demographics, and reporting of adverse events will facilitate more trustworthy interpretation of probiotic study results and inform evidence-based guidelines.